2003
DOI: 10.1017/s1047951103001112
|View full text |Cite
|
Sign up to set email alerts
|

Progressive dilation of the diameter of the aortic root in adults with a bicuspid aortic valve

Abstract: Background: To determine the rate of progression of dilation of the aortic root in adults with a bicuspid aortic valve. Methods: We reviewed retrospectively the transthoracic echocardiograms of 50 adults with a bicuspid aortic valve. Each patient had had at least two examinations made 12 months apart. Measurements were taken at four levels: at the basal attachment of the leaflets of the valve within the left ventricular outflow tract, at the widest point of the sinuses of Valsalva, at the sinutubular junction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 21 publications
3
12
1
Order By: Relevance
“…It is worthy of note that mean sinus diameter in the bicuspid subgroup of the present series was 3.8 cm, a normal value for the mean age and body surface of our bicuspid patients. Consistently, in previous studies on younger patients with bicuspid valve the most frequent site of dilatation and the site of maximal annual growth rate was the ascending tract [16,20,21]. From a clinical point of view, our findings could provide a rationale for the high freedom from aortic re-dilatation previously reported in the follow-up after surgical treatment of bicuspid-associated aneurysms using techniques that leave the native root untreated, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…It is worthy of note that mean sinus diameter in the bicuspid subgroup of the present series was 3.8 cm, a normal value for the mean age and body surface of our bicuspid patients. Consistently, in previous studies on younger patients with bicuspid valve the most frequent site of dilatation and the site of maximal annual growth rate was the ascending tract [16,20,21]. From a clinical point of view, our findings could provide a rationale for the high freedom from aortic re-dilatation previously reported in the follow-up after surgical treatment of bicuspid-associated aneurysms using techniques that leave the native root untreated, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…When z scores are calculated for our patients with BAV, our results confirm those of adult studies in that the ascending aorta z score increases over time in patients with BAV. 20 The average rate of change of z score was 0.3928/year. This suggests that, depending on the initial z score, a follow-up interval of 2-4 years is required to detect important changes in the size of the ascending aorta.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, another study involving 514 patients comparing patients with BAV (70) to patients with TAV(445) showed that patients with BAV had a higher growth rate (0.19 cm/yr compared to 0.14 cm/yr) and higher surgical repair rate than TAV patients (72.8% vs 44.8%). In addition, a recent study at the Montreal Heart Institute showed that ascending aortas in patients with BAV had a growth rate of 0.1 cm per year 1 cm beyond the sinotubular junction [31].…”
Section: Natural Historymentioning
confidence: 99%